Students' motivation and engagement in the learning process of literature teaching using imaginative re-creation technique - Rifqi, Muhammad (Universitas Islam Sultan Agung, 2023)
This article investigates the influence of imaginative re-creation techniques on students' motivation and engagement within the context of literature teaching. Traditional pedagogical methods often struggle to maintain high student involvement in literature classes. This single-case research employed a mixed-methods approach combining observation and questionnaire data to assess students' motivation and engagement. A total of forty-five participants were involved in the study. Quantitative analysis of the questionnaires revealed an average level of motivation and engagement. However, a qualitative analysis of observations demonstrated that students exhibit a heightened sense of enthusiasm and engagement during class sessions that incorporate imaginative re-creation techniques. The findings suggest that while questionnaire responses might not fully capture the extent of students' enthusiasm, the classroom atmosphere is positively affected by the implementation of imaginative re-creation techniques. This implies that students' active participation and emotional connection with the literature are better reflected in their in-class behaviors than in self-reported questionnaire responses. In conclusion, this article highlights the complex relationship between students' self-reported motivation and engagement and their observable behavior during literature classes incorporating imaginative re-creation techniques. It underscores the need for a comprehensive assessment considering quantitative and qualitative data to understand students' educational experiences better. By integrating imaginative re-creation techniques into literature teaching, educators can foster a dynamic and engaging learning environment that goes beyond average questionnaire results and cultivates a genuine passion for literary exploration among students.